Experimental study of heat transfer inside a real scale innovative air solar collector. Issue 1 (May 2021) - Sima, C; Teodosiu, C; Croitoru, C; Bode, F
Abstract: The study is performed on a glazed transpired solar collector, investigating the effect of different distances between the glazing and the absorber (30, 50, 70, and 100 mm) for different airflow values. The results show that the best solution among the tested configurations is with 30 mm distance between the glazing and absorber, no matter what the air flow rate is. The efficiency of the GTC in this case is 16-19% higher for air flow rates around 100 m3/h, m2 and even 30-40% higher for air flow rates around 150-200 m3/h, m2 – compared to configurations with larger distance between the glazing and absorber.